Sorafenib treatment following hematopoietic stem cell transplant in pediatric FLT3/ITD acute myeloid leukemia. Issue 6 (8th February 2015) - Tarlock, Katherine; Chang, Bill; Cooper, Todd; Gross, Thomas; Gupta, Sumit; Neudorf, Steven; Adlard, Kathleen; Ho, Phoenix A.; McGoldrick, Suzanne; Watt, Tanya; Templeman, Tina; Sisler, India; et al.
<x xml:space="preserve">Abstract</x> Background FLT3/ITD is associated with poor outcomes in adult and pediatric acute myeloid leukemia (AML). Allogeneic hematopoietic stem cell transplantation (HSCT) can improve cure rates, however relapse is still common. Recent studies demonstrate the activity of FLT3 inhibitors, including sorafenib, in targeting the underlying mutation. Procedure We conducted a retrospective study of 15 pediatric patients with FLT3/ITD+ AML treated with sorafenib within 18 months after receiving HSCT. Sorafenib was administered either as prophylaxis in patients considered at very high risk for relapse (n = 6) or at the time of disease recurrence (n = 9). Results Sorafenib was initiated at a median of 100 days post HSCT. Overall, 11/15 (73%) of patients experienced medically significant toxicities. Among patients who experienced toxicity, 6/11 (55%) received treatment at doses above what was later determined to be the maximum tolerated dose of sorafenib for pediatric leukemia. Importantly, sorafenib did not appear to exacerbate graft versus host disease. Our findings suggest that sorafenib may be of particular efficacy in patients with minimal residual disease (MRD); all patients who received sorafenib for MRD immediately prior to transplant or with emergence post‐HSCT are alive and remain in complete remission at a median of 48 months post HSCT. Conclusions Our case series suggests that sorafenib administration is feasible and tolerable in pediatric FLT3/ITD+ AML patients early post HSCT. Ongoing prospective controlled studies are needed to further define the dosing of sorafenib in the post‐HSCT period and to determine the optimal context for this treatment approach. Pediatr Blood Cancer 2015;62:1048–1054. © 2015 Wiley Periodicals, Inc.